From strengths to weaknesses: guiding students in their development of oral skills (2003)
This article intends to report on a small research project carried out with a group of adult EFL learners at the National University extension program, in Bogotá. Founded on a needs analysis process, some activities based on students’ strengths were proposed and developed in order to meet the students’ main need: oral skills. The proposal was implemented and evaluated revealing oral portfolios and debates as useful tools in the development of oral proficiency as well as support in students’ self-regulation processes. Key words: Adult Second Language Acquisition-Methodology-Evaluation, English- Teaching-Evaluation, Oral Communication-Teaching-Methodology, Teaching Adults- Programs El objetivo del presente artículo es dar a conocer un proyecto de investigación a pequeña escala, desarrollado con un grupo de estudiantes adultos de inglés como lengua extranjera en la Unidad de Extensión de la Universidad Nacional de Colombia, en Bogotá. A partir de un proceso de análisis de necesidades, se plantearon y desarrollaron algunas actividades basadas en las fortalezas de los estudiantes con miras a suplir la principal necesidad de los estudiantes: las habilidades orales. La implementación y evaluación de la propuesta mostró que los portafolios y los debates son herramientas claves en el desarrollo de la proficiencia así como en el apoyo de los procesos de autorregulación de los estudiantes. Palabras claves: Adquisición de una segunda lengua-Metodología-Evaluación, Inglés-Enseñanza-Evaluación, Comunicación oral-Enseñanza-Metodología, Educación de adultos-Programas